1955
DOI: 10.1677/joe.0.0120174
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Growth Hormone and Corticotrophin Upon the Adrenal Weight and Adrenocortical Mitotic Activity in the Hypophysectomized Rat

Abstract: SUMMARY 1. Treatment of rats 17–24 days after hypophysectomy with pituitary growth hormone for 3 days causes a definite, although limited, increase in adrenal weight. When growth hormone and corticotrophin are given simultaneously, the increase in adrenal weight is greater than the sum of the effects with the hormones separately. The larger the dose of corticotrophin the greater the synergic effect. 2. The action of growth hormone on the adrenal is characterized by a striking stimulation of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1968
1968
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In addition, during this period, the adre nal is relatively insensitive to ACTH. This adrenal refracbeen shown to increase adrenal sensitivity [5], and the adrenals of hypophysectomized adult animals are refrac tory to stimulation by ACTH [6], AC'TH has trophic ef fects at the level of the adrenal, including an up-regulation of its own receptors [7], and an increase in the activity of enzymes involved in the steroidogenic pathway [8].…”
mentioning
confidence: 99%
“…In addition, during this period, the adre nal is relatively insensitive to ACTH. This adrenal refracbeen shown to increase adrenal sensitivity [5], and the adrenals of hypophysectomized adult animals are refrac tory to stimulation by ACTH [6], AC'TH has trophic ef fects at the level of the adrenal, including an up-regulation of its own receptors [7], and an increase in the activity of enzymes involved in the steroidogenic pathway [8].…”
mentioning
confidence: 99%
“…The possibility that such a factor may act on adrenocortical cells in vivo is supported by a number of experiments demonstrating growth in response to factors other than ACTH. Growth hormone has been implicated as an adrenal growth stimulator (41) and an adrenal weight-maintaining factor distinct from ACTH was demonstrated in patients with Cushing's syndrome (42). In addition, neural stimulation of the adrenal results in growth by an ACTH-independent mechanism (43,44).…”
mentioning
confidence: 99%
“…Growth hormone has previously been shown to increase the mitotic index [38] and DNA content [4] of the adrenal gland, while maintaining the RNA/DNA ratio normal; it has been proposed that this growth may be mediated by somatomedins [8]. Cater and Stack-Dunne [6] have demonstrated that the action of GH on the adrenal is characterized by a striking stimulation of cell division with relatively little effect on adrenal weight. Zieleniewski [40] has reported that GH stimulates the regeneration process after adrenal enucleation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…of Physiology, Southern Illinois University, Carbondale, IL, USA Offprint requests to: A. Lewifiski, MD (address see above) fibroblast growth factor (FGF), or angiotensin II has been well documented (for review see [10]), however, ACTH can exert both mitogenic effect when applied in vivo [14,19] and antimitotic action in cell [13,20] and organ culture (Sewerynek et al, unpublished observations) of the adrenals. In some other studies the role of prolactin (Prl) [3] and growth hormone (GH) [4,6], as the stimulators of adrenal growth, has been reported. The specific Prl-binding sites in the mouse adrenal have been shown [22].…”
Section: Introductionmentioning
confidence: 99%